POET. THINKER. CITIZEN (to the 80th anniversary of the birth of Stepan Pushyk) - Slonovska, Olga (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2023)
The article provides an overview of the life and work of the outstanding writer, folklorist and researcher "Slovo o polku Ihorevim ...". During his difficult, but fulfilling and stormy life, he helped many people a lot, if not with advice, then with personal intervention in unfavorable circumstances, with a kind word, with moral support. Stepan Hryhorovych Pushyk (1944 - 2018) is a significant figure in Ukrainian literature and literary studies. His creative and scientific legacy is a multifaceted and profound phenomenon. During his lifetime, Pushyk was considered a walking encyclopedia: he knew so much about various spheres of Ukrainian folk life and history that even full professors and academicians did not know (and apparently still don't know). The topic of Stepan Pushyk's PhD thesis, which was fully consistent with his doctoral dissertation, was "Slovo o polku Ihorevim..." and Slavic Mythology" (1991). However, scientific research did not end with this work. Pushyk's research "The Bloody Wedding on Kayal" (about the "dark" places in "Slovo o polku Ihorevim") can be considered a scientific discovery. The intuition of Stepan Hryhorovych was also phenomenal, as his innate workaholism was, because even a few hours before his death he was still working on an article for the magazine "Dzvin", and the poet's last poem ("Parashka") was dated August 1, 2018. As a writer, Stepan Pushyk is a unique personality. The peculiar "folklore" method of narrative, initiated by Pushyk in his novel The Galician Gate and The Guardian Mountain, found many followers: it was picked up by V. Skurativsky and F. Zubanych. The novel from the mouths of the people itself turned out to be an innovative genre. His books of short stories and novellas "The Potion Key" and "Darabs Sail into Legend" were published in foreign languages. In general, Stepan Pushyk's works have been translated into Chinese, Romanian, Moldovan, Belarusian, Lithuanian, Kyrgyz, Bashkir, Slovak, Nepalese, and Russian. Stepan Pushyk was awarded the Taras Shevchenko State (now it is the National) Prize in Literature for "Strazh-Hora" and "Galician Gate". Stepan Pushyk published the collections “The Little Starling” and “The Golden Boat” for children.